Engagement with English Educational Materials in Physiotherapy Students : A Motivation-Based Approach - Noviyanti Riendrasiwi (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2025)
This study examines in depth how English learning motivation plays a role in influencing the level of engagement of physiotherapy students with English-language educational materials. The theoretical basis of this study refers to Self-Determination Theory, which emphasizes intrinsic and extrinsic motivational aspects, and Gardner's socio-educational model, which highlights the difference between integrative and instrumental motivation in second language learning. This study involved 44 students of STIKES Bethesda Yakkum Yogyakarta who had taken at least one semester of English for Specific Purposes (ESP). The research design used a quantitative correlational approach, with data collection through a standardized questionnaire that measured integrative motivation, instrumental motivation, and the level of student engagement with English-language academic learning resources. The results showed that integrative motivation had a significant positive correlation with student engagement (r = 0.56, p < 0.01), while instrumental motivation also showed a significant positive correlation (r = 0.62, p < 0.01). Multiple regression analysis indicated that both were significant predictors of engagement, with instrumental motivation being slightly more dominant in explaining variance in engagement (β = 0.40, p < 0.001). This suggests that physiotherapy students are more motivated to use English-language academic materials when motivated by practical needs such as professional career preparation and global communication. This finding confirms that motivation is a key factor that can drive student engagement with English-language academic content. Practical implications of this study include the need for contextualized ESP learning strategies, career-relevant curriculum design, and institutional policies that support increased student exposure to international academic materials to strengthen global competency.